Perbandingan Morfometrik Kerbau Lumpur (Bubalus bubalis) Jantan dan Betina Prasapih Pada Pemeliharaan Semi Intensif di Desa Surajaya - Fauziyah, Safna Zahara; Himmatul Hasanah (Universitas Djuanda, 2025)
Buffaloes are potential livestock that are widely developed and cultivated by the community because of their role as meat producers and their role in the economy and culture in rural areas. Buffaloes as potential livestock need to be conserved for their genetic resources so that their existence and biodiversity can be maintained. The genetic quality of a livestock can be known through the measurement of body morphometrics of livestock that are in the growth period because their body performance is still dominantly influenced by parental factors and inherited genetics. This study aims to analyze the comparison of morphometric characters between male and female pre-weaning buffaloes and their conformity with SNI in semi-intensive rearing system in Surajaya Village. The research method was quantitative observation with the object being pre-weaning buffaloes with 12 males and 5 females determined through purposive sampling and then analyzed using t-test. The observed variables included chest circumference, height, body length, body weight, and body ratio. The results showed that all morphometric parameters were not significantly different (p>0.05) between male and female buffaloes and body measurements that met the SNI requirements for swamp buffaloes included chest circumference and body height of male buffaloes. Meanwhile, body measurements that do not meet the SNI for swamp buffaloes include the body length of male and female buffaloes, as well as the chest circumference, body length and body height of female buffaloes.